The OPTIMALISASI KONDUKTIVITAS TERMAL BETON BERPORI MELALUI INOVASI MATERIAL BERBASIS ABU SEKAM PADI DAN SERAT KELAPA SEBAGAI BAHAN TAMBAH RAMAH LINGKUNGAN: Indonesia - Irene Vista Simanjuntak; Sudarno P Tampubolon; Pinondang Simanjuntak (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2025)
The purpose of this study is to increase the thermal conductivity of pervious concrete by adding environmentally friendly supplemental materials, such as coconut fibre and rice husk ash (RHA). The material variations include RHA at 0%, 5%, 10%, and 15% by cement weight and coconut fiber at 0%, 0.5%, and 1% by total mix weight. Five selected combinations were analyzed based on the balance between workability, strength, and thermal performance. Tests conducted include slump (workability), compressive strength (at 28 days), thermal conductivity, water absorption, and freeze-thaw resistance. The results indicate that the addition of RHA and coconut fiber reduces workability but significantly enhances compressive strength and freeze-thaw durability. Thermal conductivity decreased by up to 23% in the mix with 15% RHA and 1% fiber, indicating improved thermal insulation capacity. While water absorption increased with higher fiber content, it was reduced by the presence of RHA. The optimal combination was found in the mix with 10% RHA and 1% coconut fiber, which offered the best balance between mechanical strength, thermal efficiency, and environmental durability. Keywords: Coconut fiber; eco-friendly concrete; pervious concrete; rice husk ash; thermal conductivity